Estratégias de gerenciamento da capacidade e demanda em serviços públicos: um estudo aplicado em uma rota de um sistema de travessias litorâneas - Marmo, Fellipe Babbini (2018)
The present study aims to address strategies for capacity and demand management in transportation services which have restrictions and operational limitations. It presents and discusses the different practices found in literature with specific application to a passengers waterway transportation system in São Paulo State. For this, it uses as model the impact’s analysis of such practices application of capacity and demand management in the offered services. Nowadays, the unbalance between supply and demand plus lack of incentives to diversify the modal matrix of transport in large urban centers, have a direct impact on transport services quality provided in all modal. The waterway passengers transportation system of São Paulo State does not deviate from described national scenario, where the difference between supply and demand end up overloading it on specific routes, causing service’s quality reduction and translating into extensive queues to users. Considering the particularities of supply and demand of ferries’ service, as well as the high fixed cost and the inflexible tariff structure, emerged the following question of this study: how the specifics strategies application from capacity and demand management can impact the quality perceived by users of a coastal crossing system route? In order to reach an answer, this study aimed to understand which strategies could impact the quality perceived by users, focusing on waiting time, in an specific route of the system. For this, the work adopted a qualitative approach, based on the strategy of applied case study, grounded on documental analysis of the coastal crossing system and interviews content analysis. The outcome of the study indicated which strategies may have a positive impact on route quality, with a reduction in queuing time, besides identifying possible challenges, restrictions and practices that may help in future application of these strategies.